Perhitungan Biaya Produk Berdasarkan Activity Based – Costing - Julia Rafika; Muhammad Rizky Ramadhan; Saidatul Mardiyah; Wira Anggara Hadi Jamak; Isra Hayati (AKUNTANSI 45, 2024)
Activity-based costing (ABC) is an important method of determining manufacturing costs that focuses on the activities involved in the production process. This article aims to present a review based on a literature review related to the application of the ABC method in product costing, along with an explanation of the steps for calculating product cost by this method. In addition, this study also analyzes the results of applying the ABC method in increasing the accuracy and transparency of product cost calculations Operational costing (ABC) is an important method of determining production costs that focuses on the activities involved in the production process. This article aims to make comments on the basis of an overview of documents related to the application of ABC method in product costing, as well as explain the steps to calculate product cost by this method. Data from various related studies, articles and books are used to form a basic understanding of the practical steps in calculating product cost by ABC . method. Literature review is also used to identify the benefits and results of applying this method in increasing the company's production efficiency. The results of the literature review show that the application of the ABC method can produce a more accurate and transparent product cost calculation. With the ABC method, companies can identify the level of contribution of each activity in the production process, thus enabling management to determine the cost of products more precisely .